Territorial marketing as a lever for sustainable tourist attractiveness: the case of the imperial city of Meknes - FAREH Morad; KARIM Kaoutar; IDRISSI Khadija; CHARRASS Abdelmajid (African Scientific Journal, 2025)
Abstract: This article examines how territorial marketing can enhance the tourist attractiveness of the imperial city of Meknes while promoting sustainable development. The research adopts a qualitative methodology, based on 13 semi-structured interviews conducted with three groups of participants: tourism professionals (5), institutional and community stakeholders (3), and domestic and international visitors (5). This approach made it possible to capture diverse perspectives on Meknes’s image, sustainable tourism initiatives, and governance practices. The findings reveal three major results: (1) Meknes suffers from an unclear and poorly differentiated brand image compared to other Moroccan destinations; (2) sustainable tourism initiatives exist but remain fragmented and lack visibility; (3) effective collaboration between stakeholders is still weak, limiting the coherence of local territorial marketing strategies. These results suggest that repositioning Meknes as a sustainable destination requires the development of a coherent brand identity, greater visibility of sustainability projects, and strengthened multi-stakeholder governance. Keywords: Territorial marketing, sustainable tourism, attractiveness, local governance, brand image Résumé : Cet article analyse comment le marketing territorial peut renforcer l’attractivité touristique de la ville impériale de Meknès tout en favorisant un développement durable. La recherche adopte une approche qualitative, fondée sur 13 entretiens semi-directifs réalisés auprès de trois groupes de participants : professionnels du tourisme (5), acteurs institutionnels et communautaires (3), et visiteurs nationaux et internationaux (5). Cette méthodologie a permis de recueillir des perceptions variées sur l’image de Meknès, les initiatives en matière de tourisme durable et les pratiques de gouvernance. Les résultats mettent en évidence trois constats principaux : (1) Meknès souffre d’une image de marque peu claire et mal différenciée par rapport aux autres destinations marocaines ; (2) les initiatives de tourisme durable, bien que présentes, demeurent dispersées et peu visibles ; (3) la collaboration entre acteurs reste limitée, ce qui affaiblit la cohérence des stratégies locales de marketing territorial. Ces résultats suggèrent que le repositionnement de Meknès en tant que destination durable passe par la création d’une identité de marque cohérente, une meilleure visibilité des projets de durabilité et un renforcement de la gouvernance partenariale. Mots-clés : Marketing territorial, tourisme durable, attractivité, gouvernance locale, image de marque​